Protection of customer private property rights in the digital finance ecosystem: A due process of law analysis of the authority to block accounts by the financial services authority - Fadhlillah Rifqi Hazazi (Journal of Law, Administration, and Social Science, 2026)
The rapid development of the digital financial ecosystem has triggered an increase in state interventions against citizens' digital assets to enforce financial stability and combat cybercrime. Administrative actions such as the blocking of customer accounts by the Financial Services Authority (OJK) inherently intersect directly with the boundaries of protecting the right to property guaranteed by the constitution. This study aims to analyze the legality and accountability of OJK's authority in blocking customer accounts from a Human Rights law perspective, specifically the fulfillment of the due process of law principle. Utilizing normative legal research methods with statutory and conceptual approaches, this study finds that the execution of administrative discretion by OJK in conducting account blocks often disregards the procedural rights of customers, such as the right to be heard and the right to legal certainty, thereby creating an asymmetrical position between the state and citizens. The analysis concludes that to achieve substantive justice, a regulatory reconstruction is required to integrate judicial review mechanisms and transparent operational procedures to limit the potential abuse of power by financial services authorities.The rapid development of the digital financial ecosystem has triggered an increase in state interventions against citizens' digital assets to enforce financial stability and combat cybercrime. Administrative actions such as the blocking of customer accounts by the Financial Services Authority (OJK) inherently intersect directly with the boundaries of protecting the right to property guaranteed by the constitution. This study aims to analyze the legality and accountability of OJK's authority in blocking customer accounts from a Human Rights law perspective, specifically the fulfillment of the due process of law principle. Utilizing normative legal research methods with statutory and conceptual approaches, this study finds that the execution of administrative discretion by OJK in conducting account blocks often disregards the procedural rights of customers, such as the right to be heard and the right to legal certainty, thereby creating an asymmetrical position between the state and citizens. The analysis concludes that to achieve substantive justice, a regulatory reconstruction is required to integrate judicial review mechanisms and transparent operational procedures to limit the potential abuse of power by financial services authorities.